Analisis Pergerakan Partikel terhadap Rekaman Mikrotremor di Permukaan Sungai Bawah Tanah Bribin, Kawasan Karst Gunung Sewu - Kholis Nurhanafi; Ahmad Zarkasi; Sahara Hamas Intifadhah; Nugroho Budi Wibowo; Aditya Yoga Purnama (Universitas Andalas, 2023)
Microtremor has been widely used to determine soil characteristics and dynamics. In this research, particle motion analysis was conducted on 15 microtremor data recordings around the surface of the Bribin Underground River in the Gunungsewu Karst Area. Spectrum analysis was conducted as a basis for determining the frequency range for the particle motion analysis process. Particle motion analysis was only carried out on the horizontal component of the microtremor signal which is expected to provide a representation of the river flow path. The results of particle motion analysis of microtremor recordings in the surface area of the Bribin Underground River show that there are only two points that have a motion-resultant oriented to certain direction, which is perpendicular to the river channel.The points are A4 and B4 which are located in the eastern part of the river flow path.